Rejuvenation of spent fuel in the force-free helical reactor (FFHR) - Yapici, H; Gökçek, M (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
This study considers spent fuel rejuvenation potential of the force-free helical reactor (FFHR), which is a relevant heliotron-type D-T fusion reactor. For this purpose, three different spent fuels were selected, i.e.: (1) CANDIJ, (2) PWR-UO2, and (3) PWR-MOX spent fuels. The spent fuel (volume fraction of 60%), spherically prepared and cladded with SiC (volume fraction of 10%), was located in the fuel zone (FZ) in the blanket of the FFHR. The FZ was cooled with high-pressured helium gas (volume fraction of 30%) for the nuclear heat transfer. The neutronic calculations were performed by solving the Boltzmann transport equation with the help of the neutron transport code XSDRNPM-S/SCALE4.3. The calculations of the time dependent atomic densities of the isotopes were performed for an operation period (OP) of up to 4 years by 75%, plant factor (n) under a first-wall neutron load (P) of 1.5 MW/m(2). The temporal variations of the atomic densities of the isotopes in the spent fuel composition and other physical parameters were calculated for a discrete time interval (At) of 1/12 year (one month), by using the interface program (code). In all investigated spent fuel cases, the tritium self-sufficiency is maintained for DT fusion driver along the OP. The CANDU spent fuel becomes usable in a conventional CANDU reactor after a regeneration time of similar to6 months. The CFFE value approaches 3.5% in the blanket fuelled with the PWR-UO2 and -MOX spent fuels after 40 and 34 months, respectively. The plutonium component can never reach a nuclear weapon grade quality during spent fuel rejuvenation. Consequently, the blanket has high neutronic performance for the rejuvenation of the spent fuels. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: FUSION-REACTOR; FLIBE BLANKET; DESIGN; TRANSMUTATION; PERIOD; Nuclear Science & Technology